2003
DOI: 10.1182/blood-2002-08-2512
|View full text |Cite
|
Sign up to set email alerts
|

Free radical stress in chronic lymphocytic leukemia cells and its role in cellular sensitivity to ROS-generating anticancer agents

Abstract: 2-Methoxyestradiol (2-ME), a new anticancer agent currently in clinical trials, has been demonstrated to inhibit superoxide dismutase (SOD) and to induce apoptosis in leukemia cells through a free radicalmediated mechanism. Because the accumulation of superoxide (O 2 ؊ ) by inhibition of SOD depends on the cellular generation of O 2 ؊ , we hypothesized that the endogenous production of superoxide may be a critical factor that affects the antileukemia activity of 2-ME. In the present study, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
206
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(224 citation statements)
references
References 51 publications
16
206
0
2
Order By: Relevance
“…So cancer cells are more sensitive to ROS-generating anticancer agents (Zhou et al, 2003). Our study demonstrated emodin could provoke oxidative stress in HCT116 cells.…”
Section: Discussionmentioning
confidence: 58%
“…So cancer cells are more sensitive to ROS-generating anticancer agents (Zhou et al, 2003). Our study demonstrated emodin could provoke oxidative stress in HCT116 cells.…”
Section: Discussionmentioning
confidence: 58%
“…By bypassing the anti-apoptotic machinery, 6,7,17 RXL is able to induce caspase-independent cell death in CD40-stimulated CLL cells that are resistant to various drugs as result of upregulation of Bcl-2 family members. 5,6 Moreover, our findings suggest that it might be very relevant to combine rituximab with other ROS-inducing drugs like arsenic trioxide 56 or cisplatin. 59 …”
Section: Discussionmentioning
confidence: 78%
“…55 Rituximab-induced ROS production was impaired in the presence of EGTA, supporting our hypothesis that Ca 2 þ is important for rituximab-induced ROS. Zhou et al 56 showed that CLL cells with higher basal ROS are more sensitive to 2-Methoxyestradiol, a compound that induces apoptosis via a free radical-mediated mechanism. On the basis of our data, we propose that CD40 stimulation sensitizes CLL cells to rituximab-mediated death by increasing basal ROS production, which is further increased by rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…For example, adenine deoxynucleoside analogs commonly used for treating some lymphoid malignancies such as cladribine and 2-chlororo-2 0 -ara-fluorodeoxyadenosine (Genini et al, 2000) and arsenic trioxide, an old cytotoxic agents that proved efficient in treating acute promyelocytic leukemia (Kroemer and de The, 1999;Larochette et al, 1999;Sordet et al, 2001). In acute promyelocytic leukemia cells, cellular toxicity of arsenic trioxide appears to mainly result from increased production of ROS, leading to the opening of the permeability transition pore complex, a decrease in mitochondrial membrane potential, cytochrome c release and caspase activation (Zhou et al, 2003;Chou et al, 2004). Ascorbic acid can enhance the efficacy of arsenic trioxide by reducing intracellular glutathione concentrations and this combination is currently tested in elderly patients with acute myeloid leukemia when these patients are not able to withstand intensive chemotherapy.…”
Section: Mitochondria As a Target For Treating Hematopoietic Cell Dismentioning
confidence: 99%